Contribution à l’étude de la qualité et la stabilité d’un lait fermenté alicament additionné d’extrait à l’éthanol de Thymus vulgaris (Thym) récolté dans la région de Naama - Benrabah, Hanen; Dekichene, Mohamed (My University, 2017)
This study aimed to determine the effect of incorporation of the Thym ethanol extract on the quality and stability of a fermented milk (yoghurt type) during 2 periods of the study, 4 hours of fermentation and 21 days storage at 4 ° C. The experimental samples were prepared at different doses of the Thym extract (0%, 2%, 4%, 6%, 8%), the following measurements and controls were carried out in triple tests on each processed product: dornic acidity, PH, viscosity, acid taste, taste of freshness, cohesiveness, adhesiveness, taste, odor, color. During storage it appears that the acidity is inversely proportional to the incorporation rates of the extract with Thym ethanol; While the pH follows an inverse evolution in the products according to the extract levels added. The addition of Thym ethanol extract at particularly severe levels of 8% affects the viscosity of the products which decreases relatively as compared to the control yoghurt. Thym ethanol extracts induced a highly significant decrease in the growth of Streptococcus thermophilus and Lactobacillus bulgaricus. The number of these germs, however, remains comparable to that of standard yoghurt (10P6P live organisms / ml). The tasters rated the taste, smell, acidity, aftertaste, adhesiveness, cohesiveness of the fermented milks and Thym ethanol extract as acceptable.
Keywords: Lait fermenté; Thym (Thymus vulgaris); Streptococcus thermophilus; Lactobacillus bulgaricus.; Fermented milk